Criteria for prioritization of HIV programs in Viet Nam: a discrete choice experiment - Ali Safarnejad; Milena Pavlova; Vo Hai Son; Huynh Lan Phuong; Wim Groot (BMC, 2017)
Abstract Background With the decline in funding for Viet Nam's response to the HIV epidemic, there is a need for evidence on the criteria to guide the prioritization of HIV programs. There is a gap in the research on the relative importance of multiple criteria for prioritizing a package of interventions. This study elicits preferences and the trade-offs made between different HIV programs by relevant stakeholders and decision-makers in Viet Nam. It also pays attention to how differences in social and professional characteristics of stakeholders and their agency affiliations shape preferences for HIV program criteria in Viet Nam. Methods This study uses self-explicated ranking and discrete choice experiments to determine the relative importance of five criteria - effectiveness, feasibility, cost-effectiveness, rate of investment and prevention/treatment investment ratio - to stakeholders when they evaluate and select hypothetical HIV programs. The study includes 69 participants from government, civil society, and international development partners. Results Results of the discrete choice experiment show that overall the feasibility criterion is ranked highest in importance to the participants when choosing a hypothetical HIV program, followed by sustainability, treatment to prevention spending ratio, and effectiveness. The participant's work in management, programming, or decision-making has a significant effect on the importance of some criteria to the participant. In the self-explicated ranking effectiveness is the most important criterion and the cost-effectiveness criterion ranks low in importance across all groups. Conclusions This study has shown that the preferred HIV program in Viet Nam is feasible, front-loaded for sustainability, has a higher proportion of investment on prevention, saves more lives and prevents more infections. Similarities in government and civil society rankings of criteria can create common grounds for future policy dialogues between stakeholders. Innovative models of planning should be utilized to allow inputs of informed stakeholders at relevant stages of the HIV program planning process.